If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4t + 9) + -1(-2 + 7) = 0 Reorder the terms: (9 + 4t) + -1(-2 + 7) = 0 Remove parenthesis around (9 + 4t) 9 + 4t + -1(-2 + 7) = 0 Combine like terms: -2 + 7 = 5 9 + 4t + -1(5) = 0 Multiply -1 * 5 9 + 4t + -5 = 0 Reorder the terms: 9 + -5 + 4t = 0 Combine like terms: 9 + -5 = 4 4 + 4t = 0 Solving 4 + 4t = 0 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 4t = 0 + -4 Combine like terms: 4 + -4 = 0 0 + 4t = 0 + -4 4t = 0 + -4 Combine like terms: 0 + -4 = -4 4t = -4 Divide each side by '4'. t = -1 Simplifying t = -1
| A=p+pnr | | p-10=25 | | 8=n-65 | | 52q=32 | | b^4-ab^3+b^2c=0 | | 7*cos^2*x-cos*x-8=0 | | 71=-9n+8 | | 3*cos*2*x-5*cos*x-1=0 | | -3(y-2)=-5y+18 | | 7w-9=5(w+1) | | 7(y+6)-2y=2 | | 22-2x=14 | | .5x-2.4=.6 | | -4v+8(v-2)=-4 | | -3(4t-3)+5t=6t-5 | | 48+x(9+3)=288 | | 7u+5=5 | | -4v+8(v+2)=-4 | | 8g-7=-39 | | 3y+2f-f+1-3y+7=32 | | 2k+5=3 | | -5n+3=-4n-4 | | -6=-6w+4(w+3) | | 4b^2-169y^2= | | 9x+3x=10101010101001101 | | c+bc-11c-4=13c+4-2 | | 2k+10=k+15 | | (8/t-7)-3/t | | 15=2a-2 | | 18+6x+x^2=0 | | 5x-5y=10z | | -4/35/8/7 |